Integrasi Sistem Akuaponik IoT Dengan Aplikasi Mobile Untuk Pemantauan Jarak Jauh - Aulia Sabila; Dwi Jaka Pratama; Febry Yansha; Indra Dwisaputra; Sidhiq Andriyanto (BETRIK, 2025)
The 79.93% growth of the urban population and the decline of agricultural land in Indonesia demand efficient, sustainable agricultural solutions. Aquaponics systems traditionally require intensive manual monitoring of environmental parameters such as pH, temperature, and nutrient levels, which is impractical for time-constrained urban farming. Conventional approaches face several constraints, including delayed detection of critical parameter changes, the risk of human error in manual sensor readings, inconsistent maintenance schedules, and the mobility limitations of users who must always be physically present on-site. This research aims to design and implement an integrated Internet of Things (IoT)-based aquaponics system with an Android mobile application as a solution to overcome these limitations through real-time remote monitoring and control. The Extreme Programming (XP) method was used to support rapid iteration and active user involvement in system development. The system was built using pH, temperature, nutrient, and water level sensors, along with an automatic fish feeder, connected to an Arduino Mega and ESP32. Data is transmitted to Firebase and displayed via a Kotlin-based Android application. Black-box testing confirmed the system's 100% validity for all functions (login, real-time monitoring, actuator control, and history). Sensor accuracy testing showed success rates between 94.40% and 99.54%, proving the system operates stably and accurately for remote monitoring, making it an innovative, digitally-managed aquaponics solution that successfully addresses all limitations of conventional systems